(3GdGOGQI GdGSJQGJjLjI h JfejI GdehGQO GdHTQjIs - (3eMeO SejQ(B, (3CMeOs ((3YeGf(B:s (3OGQ GdeSjQI ddfTQ h GdJhRjY(B,s, 2009)
(3GdEOGQI GdGSJQGJjLjI, JfejI GdehGQO GdHTQjI, GdGfJGLjI aj GdehGQO GdHTQjI, GdJNWjW GdGSJQGJjLj ddJShjb GdGdcJQhfj, GdJShjb GdGdcJQhfj ef efXhQ GdeONd GdSHQGfj, GdJShjb GdGdcJQhfj ef efXhQ GdeONd GdJMhjdj, GdJShjb GdGdcJQhfj ef efXhQ GdeONd GdefXhej, CKQ GdJShjb GdGdcJQhfj Ydi GdbOQI GdJfGaSjIs
(3HHdjhZQGajG(B: (3U(B.332s
Keywords: (3GdGOGQIs; (3GdGSJQGJjLjIs; (3GdGfJGLs; (3GdeQGbHIs